Differences in the Ageing Behavior of Asphalt Pavements with Porous and Stone Mastic Asphalt Mixtures. Issue 12 (December 2021) - Jing, Ruxin; Varveri, Aikaterini; Liu, Xueyan; Scarpas, Athanasios; Erkens, Sandra
The degradation of bituminous materials as a result of ageing has a significant effect on asphalt pavement performance. In this study, one porous asphalt (PA) section and one stone mastic asphalt (SMA) asphalt pavement section were designed and constructed in 2014 and exposed to the actual environmental condition. To study the change in the pavement's mechanical properties, asphalt cores were collected from both test sections annually. The change in stiffness modulus was determined via cyclic indirect tensile tests. To investigate the ageing behavior across the pavement depth, the bitumen was extracted and recovered from 13 mm slices along the depths of the cores. The chemical composition and rheological properties of the field-recovered bitumen, and that of original bitumen aged in standard short- and long-term ageing protocols, were investigated by means of the Fourier Transform Infrared (FTIR) spectrometer and Dynamic Shear Rheometer. The results show that the effect of mineral aggregate packing, and therefore of air-void distribution and connectivity, on the ageing sensitivity of the pavements with time was significant, as the changes in the stiffness of the PA mixture were greater than that of SMA mixture. In addition, the results of field-recovered bitumen show that there is an ageing gradient inside the porous asphalt layer, however, the ageing of SMA mainly happens on the surface of the layer. Finally, the field-recovered and laboratory-aged bitumen results demonstrate a weak relation between field and standard laboratory ageing protocols.